Dampak Penggunaan Clickbait pada Judul Berita di Tribunnews.com terhadap Minat Baca Mahasiswa Ilmu Komunikasi Universitas Singaperbangsa Karawang Angkatan 2020 - Mohammada, Sheila; Mayasari, Mayasari; Budhiharti, Tri Widya (CV. ITTC INDONESIA, 2024)
This research discusses the influence of the use of clickbait headline news on Tribunnews.com on students’ reading interest. The theory used is uses and effect theory which explains that the use of media can cause many effects on an individual, The research method in this study is quantitative with aby sampling using the Non Probability Sampling method with the type of Porposive Sampling. The results of research and discussion showed that the use of clickbait headline newsdan a significant effect on students’ reading interest.